Pengurangan Masa Stratifikasi dengan Penambahan Hormon GA3 Pada Perkecambahan Benih Stroberi (Fragaria x annanassa (Weston) Duchesne) - Mayola Arda; - Suwirmen; Zozy Aneloi Noli (Jurnal Biologi Universitas Andalas, 2014)
An experiment on the reduction of stratification period with addition of GA3 hormone to strawberry (Fragaria x annanassa (Weston) Duchesne) seeds germination has been done from December 2013 to February 2014 in the Laboratory of Plant Physiology, Department of Biology, Faculty of Sciences, Andalas University, Padang. The experiment aimed to reduce the stratification period and determine the reliable concentration of GA3 on strawberries seeds germination. The experiment was conducted by using Split Plot Design which consisted of stratification levels (0 week, 1 week and 2 weeks) as main plots, while GA3 consentration (0 ppm, 25 ppm, 50 ppm and 75 ppm) as sub plots. The results from that 25 ppm GA3 combined to 0 week showed the best acceleration to  the emergence of sprouts, increased the number of seed germinations and sprouts length but did not significantly affected to the length of time required for the germination.Key word :GA3, germination, stratification, strawberry